1972
DOI: 10.1139/b72-236
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sunflower rust. X. Specialization of Puccinia helianthi on wild sunflowers in Texas

Abstract: Sunflower rust (Puccinia helianthi) was collected in Texas on wild Helianthus spp. believed to be ancestors of the cultivated sunflower (Helianthus annuus). Race 1, the least pathogenic on the standard "Canadian" differentials, was the most common. Races 1 and 2 predominated on H. annuus and H. debilis, race 2 on H. praecox, and race 4 on H. petiolaris. Most host species proved to be heterozygous for rust resistance; cross-infectivity tests between them were inconclusive. Puccinia helianthi shows a high degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Resistance genes R 1 and R 2 , which have been widely used in breeding programs, originated from outcrosses with CWR in Texas and are believed to be among the earliest resistance genes to genetically control a sunflower pathogen (Putt and Sackston, 1957, 1963). Hennessy and Sackston (1972) concluded that most species of wild sunflower in Texas were heterogeneous for rust resistance. An extensive survey of >200 populations of two annual species ( H .…”
Section: Biotic Traitsmentioning
confidence: 99%
“…Resistance genes R 1 and R 2 , which have been widely used in breeding programs, originated from outcrosses with CWR in Texas and are believed to be among the earliest resistance genes to genetically control a sunflower pathogen (Putt and Sackston, 1957, 1963). Hennessy and Sackston (1972) concluded that most species of wild sunflower in Texas were heterogeneous for rust resistance. An extensive survey of >200 populations of two annual species ( H .…”
Section: Biotic Traitsmentioning
confidence: 99%
“…Resistance genes R 1 and R 2 , which have been widely used in sunflower breeding programs, originated from outcrosses with wild sunflower in Texas and are believed to be the first resistance genes to control a sunflower pathogen Sackston, 1957, 1963). Hennessy and Sackston (1972) concluded that most species of wild sunflower in Texas were heterogeneous for rust resistance. An extensive survey of over 200 populations of seven species including two annual species, H. annuus and H. petiolaris, and five perennial species, H. maximiliani, H. nuttallii, H. grosseserratus, H. pauciflorus (rigidus) and H. tuberosus from the north central USA was undertaken by Zimmer and Rehder (1976).…”
Section: Rustmentioning
confidence: 99%
“…However, wild Helianthus species have been a good source of genes for resistance to the causal agents of economically important diseases. A vast reservoir of rust resistance genes is present in wild annuals viz., wild H. annuus, H. argophyllus and H. petiolaris (Hennessy and Sackston, 1972;Zimmer and Rehder, 1976;Thompson et al, 1981;Seiler, 1992) and in the sole perennial, H. hirsutus (Korell et al, 1996). Quresh et al (1993) observed that resistance to all four rust races (1, 2, 3 and 4) could be found in wild H. annuus, H. argophyllus and H. petiolaris.…”
Section: Introductionmentioning
confidence: 99%